2018
DOI: 10.1111/ijfs.14032
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin‐chitosan edible film activated with Boldo extract for improving microbiological and antioxidant stability of sliced Prato cheese

Abstract: The objective of this study was to produce edible gelatin-chitosan blended films containing Boldo extract, and then they were applied on sliced Prato cheese. Colour, pH, moisture and fat content parameters and antioxidant and antimicrobial activity were assessed, during storage at 4°C up to 10 days. The films did not provoke changes in fat content and pH (P < 0.05). Boldo extract incorporation in blended films (GEL50:CH50+ B) enabled significant protection against oxidation when compared with the control sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 28 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…Additionally, the antioxidant activity of milk and its products is important for extending their shelf life [26]. Processing, packaging, storage conditions and other factors have an obvious influence on the proportions of antioxidants, which is directly relevant to oxidative stability of dairy products [25] [27]. Numerous researches respecting the impact of processing on the antioxidant activity of milk and dairy products have been conducted [28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the antioxidant activity of milk and its products is important for extending their shelf life [26]. Processing, packaging, storage conditions and other factors have an obvious influence on the proportions of antioxidants, which is directly relevant to oxidative stability of dairy products [25] [27]. Numerous researches respecting the impact of processing on the antioxidant activity of milk and dairy products have been conducted [28].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are extensively used to prevent oxidation by scavenging free radical but due to augmented customer trend for additives free food products, incorporation into packaging material is the best option [40]. Antioxidants incorporation into packaging material not only prevents quality deterioration of the product but also stabilizes the polymer [41]. Synthetic antioxidants like butylated hydroxytoluene (BHT) and butylated hydroxy anisole (BHA) are conventionally used in cheese packing.…”
Section: Free Radical Scavenger or Antioxidant Incorporated Filmsmentioning
confidence: 99%
“…Sliced cheese packed in red algae films incorporated with 1% grape fruit seed extract (GFSE) showed decreased peroxide and thiobarbituric acid value indicating the antioxidant capability of GFSE [44]. Gelatin-chitosan edible film with Boldo herb extract possessed antioxidant and antimicrobial activity and had preservative effect on sliced Prato cheese by preventing psychrotrophs [41]. Similarly, other natural antioxidants like green tea extract [45], catechins [46] and rosemary extract [40] had been explored for their antioxidant potential in cheese packaging but the major challenge with antioxidant incorporated films in cheese packaging is synchronization of antioxidant diffusion rate according to cheese requirement.…”
Section: Free Radical Scavenger or Antioxidant Incorporated Filmsmentioning
confidence: 99%
“…[ 110,111 ] Azarnia et al. [ 86 ] reported that boldo extract activated with CS‐gelatin edible films has improved the antioxidant and antimicrobial strength of Prato cheese and did not trigger the fluctuations in pH and fat content. [ 86 ]…”
Section: Chitosan and Other Bio‐polymers In Edible Coating Of Cheesementioning
confidence: 99%